Effects of Cr2O3 addition on the phase, mechanical properties, and microstructure of zirconia-toughened alumina added with TiO2 (ZTA–TiO2) ceramic composite - Manshor, Hanisah; Ahmad Azhar, Ahmad Zahirani; Abd Rashid, Rashita; Sulaiman, Shazreen; Abdullah, Ezzat Chan; Ahmad, Zainal Arifin (Elsevier Ltd., 2016)
Increasing demand for stronger cutting tools has led to the development of several novel composites and other multi-phase ceramics with better properties, particularly high fracture toughness. Cr2O3 is used as new material additive in this study, as it has attracted attention due to the formation of isovalent solid solution when added to Al2O3, contributing to improved fracture toughness. Thus, the aim of this study is to investigate the effects of the addition of Cr2O3 at a concentration of between 0.0 wt% to 1.0 wt% on the physical properties, microstructural features and phase of a ZTA-TiO2 ceramics composite. The samples were prepared by wet-mixing and uniaxial compaction, then sintered for 1 h at 1600 °C under pressureless conditions. The sintered samples were then identified in terms of their density, hardness, fracture toughness and crack propagation, and were then subjected to microstructural analysis by XRD and FESEM. It was discovered that with addition of 0.6 wt% of Cr2O3 to the composite, an optimum density of 4.0630 g/cm3, hardness of 1681 HV, and fracture toughness of 7.15 MPa.m1/2 were obtained. As a result of this addition, plate-like Al2O3 grains were observed, which caused cracks formed in the composite to spread in an inter-granular manner. This confirmed that the properties of ZTA–TiO2 ceramics composite were augmented by the addition of 0.6 wt% Cr2O3.